Cross‐Sectional and Longitudinal Associations of Diffuse Idiopathic Skeletal Hyperostosis and Thoracic Kyphosis in Older Men and Women. Issue 8 (10th July 2017) - Katzman, Wendy B.; Parimi, Neeta; Mansoori, Ziba; Nardo, Lorenzo; Kado, Deborah M.; Cawthon, Peggy M.; Marshall, Lynn M.; Schousboe, John T.; Lane, Nancy E.; ,
Abstract : Objective: To investigate cross‐sectional and longitudinal associations of diffuse idiopathic skeletal hyperostosis (DISH) and thoracic kyphosis in older persons. Methods: DISH and kyphosis were assessed in 1, 500 men from the Osteoporotic Fractures in Men (MrOS) study and in 1, 267 women from the Study of Osteoporotic Fractures (SOF). DISH was assessed using baseline lateral spine radiographs, and Cobb angle of kyphosis was measured from baseline and followup radiographs, a mean 4.6 years later in men, and 3.7 and 15 years later in women. Linear regression was used to analyze associations of DISH with baseline Cobb angle and with percent annualized change in Cobb angle. We tested for heterogeneity among studies. Results: DISH was identified in 222 participants in MrOS (15%) and in 156 participants in SOF (12%). Participants with DISH in both cohorts had higher baseline Cobb angles ( P < 0.05), after adjustment for covariates. After approximately 4 years of followup, there was no significant difference in annualized percent change in Cobb angle in those with DISH compared to those without DISH ( P > 0.05) for men or women. Women with DISH had less kyphosis progression over 15 years (0.25% less annualized change in Cobb) than those without DISH. Conclusion: Prevalent DISH is associated with greater kyphosis in older men and women, and is not significantly associated with a change in kyphosis over 4–5 years. However, in women followed over 15 years, DISH was associated with less progression of kyphosis. These results suggest that DISH influences kyphosis and may slow progression over the long term. Additional studies of DISH/kyphosis associations are warranted to understand the functional implications of this finding.